2019
DOI: 10.1186/s40104-019-0325-x
|View full text |Cite
|
Sign up to set email alerts
|

Partially defatted black soldier fly larva meal inclusion in piglet diets: effects on the growth performance, nutrient digestibility, blood profile, gut morphology and histological features

Abstract: Background The aim of this trial was to investigate the effects of different inclusion levels of a partially defatted black soldier fly (BSF, Hermetia illucens L.) larva meal on the growth performance, nutrient digestibility, blood profile, gut morphology and histological features of piglets. A total of 48 newly weaned piglets were individually weighed (initial body weight (IBW): 6.1 ± 0.16 kg) and randomly allocated to 3 dietary treatments (4 boxes as replicates/treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
128
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(146 citation statements)
references
References 39 publications
15
128
2
1
Order By: Relevance
“…The effect of MCFA on morphology could be more evident the rst days PW as the VH in the small intestine seems to recover within two weeks PW [61]. Biasato et al [10] also reported no difference in intestinal morphometric indices after feeding pigs diets with up to 10% defatted BSFL. In accordance with our results, they also observed greater morphometric indices in the jejunum than the ileum.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of MCFA on morphology could be more evident the rst days PW as the VH in the small intestine seems to recover within two weeks PW [61]. Biasato et al [10] also reported no difference in intestinal morphometric indices after feeding pigs diets with up to 10% defatted BSFL. In accordance with our results, they also observed greater morphometric indices in the jejunum than the ileum.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data indicate an insect yearly production at EU level of about 6000 tonnes, corresponding to an average of 2000-3000 tonnes of insect-derived PAPs (IPIFF 2019a; Mancuso et al 2019). They are expected to be increasingly used in Europe and around the globe as a replacement for conventional animal-derived proteins for aquaculture (Lock et al 2018) and terrestrian livestocks (Bovera et al 2018;Khan 2018;Biasato et al 2019a). Forecasted insect protein production to be used in both the human food and the animal feed sectors for 2025 surpasses 1.2 million tonnes (Mt) reaching about 10% of the EU share of total protein supply (IPIFF 2019a; Mancuso et al 2019).…”
Section: Insect Mealsmentioning
confidence: 99%
“…Insects for organic waste valorisation -Some insect species can efficiently convert low value organic substrate (wastes from industry or agriculture) into high value products exalting the concept of Circular Economy and Zero Waste (Verbeke et al 2015;Bosch et al 2019;Pinotti et al 2019). In addition, they seem to have a low environmental impact in terms of land use and water consumption (Dobermann et al 2017; van Huis and Oonincx 2017), even though available environmental studies and Life Cycle Assessments (LCAs) are still limited (Mertenat et al 2019).…”
Section: Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of this article is to provide some historical perspective of the black soldier fly before its recognition as a model for recycling organic waste to produce feed for aquaculture (St. Hilaire et al, 2007), poultry (Moula et al, 2017), livestock (Biasato et al, 2019;Gasco et al, 2019), and pets (Bosch et al, 2014), or use to produce bio-energy (Surendra et al, 2016), while generating organic matter (i.e. frass) that can be used as fertiliser (Setti et al, 2019;Xiao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%